Answer:
Oh if I could hug you
Step-by-step explanation:
tysm you are the best!
Answer:
<h2>D</h2>
Step-by-step explanation:
If pair of ratios does form a true proportion then:



Substitute the first equation into the second equation. You will get:
4x - (2x - 5) = 7
Distribute the negative sign into the parenthesis:
4x - 2x + 5 = 7
Simplify
2x + 5 = 7
Subtract 5 on both sides
2x = 2
x = 1
Now, substitute x = 1 into the first equation:
y = 2(1) - 5
y = 2 - 5
y = -3
The solution to the system of equations is (1, -3).
6 because 18+6=24+6=30+6=36